Digitisation and public accessibility of old Polish guides on self-treatment and quality-of-life improvement - Nowak, Joanna (Medical Studies/Studia Medyczne, 2017)
This letter to the Editor can prove useful as a mini-guide. Interest in health and quality of life is continuing to grow in the second decade of the 21st century, both among professionals actively involved in giving advice to others and among diverse social groups, as well as individually, among those sick and those healthy. Along with recent novelties, traditional Old Polish methods also feature prominently in discussions, but those interested know relatively little about how to access source materials. This letter therefore describes the possibilities for open access to Polish-language health guides from the Renaissance and Baroque era, whose authors included medical doctors and which focused on describing food and herbs used in self-treatment and promoting the healthy life style of the period. The works of Andrzej from Kobylin, Zawacki, Śleszkowski, Olszowski and Haur are briefly described and information is given about their availability in full-text on-line data bases.